2015
DOI: 10.1080/15374416.2015.1004681
|View full text |Cite
|
Sign up to set email alerts
|

Parent Management Training and Collaborative & Proactive Solutions: A Randomized Control Trial for Oppositional Youth

Abstract: Objective Examine the efficacy of Collaborative & Proactive Solutions (CPS) in treating oppositional defiant disorder (ODD) in youth by comparing this novel treatment to Parent Management Training (PMT), a well-established treatment, and a waitlist control (WLC) group. Method One hundred and thirty four youth (ages 7 – 14, 61.9% male, 83.6% white) who fulfilled Diagnostic and Statistical Manual of Mental Disorders (4th ed.) criteria for ODD were randomized to either CPS, PMT or WLC groups. ODD was assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 33 publications
(38 reference statements)
3
62
0
1
Order By: Relevance
“…However, an increasing number of studies and meta-analyses suggest that adding PFT to CFT does not significantly improve treatment effects, again, independent of the targeted problem (e.g. Dowell and Ogles 2010;Eimecke et al 2010;Ollendick et al 2015;Silverman et al 2008;Thulin et al 2014). These findings were surprising because the clinical impression exists that involving parents in CFT ought to be beneficial (e.g.…”
Section: Traditional Cbt For Children and Adolescentsmentioning
confidence: 44%
See 1 more Smart Citation
“…However, an increasing number of studies and meta-analyses suggest that adding PFT to CFT does not significantly improve treatment effects, again, independent of the targeted problem (e.g. Dowell and Ogles 2010;Eimecke et al 2010;Ollendick et al 2015;Silverman et al 2008;Thulin et al 2014). These findings were surprising because the clinical impression exists that involving parents in CFT ought to be beneficial (e.g.…”
Section: Traditional Cbt For Children and Adolescentsmentioning
confidence: 44%
“…Also, research on the effect of PFT on children's externalizing problems suggests that PFT effects decline when the targeted children are older (e.g. Kazdin 1995;Ollendick et al 2015).…”
Section: Traditional Cbt For Children and Adolescentsmentioning
confidence: 99%
“…On the other hand, disruptive behavior may reduce compliance with psychosocial interventions for internalizing symptoms and contribute to functional impairments conferred by the primary diagnoses (Garcia et al 2010). Children with elevated symptoms of anxiety/depression demonstrate greater gains following treatment with parent training (Ollendick et al 2015) and CBT for aggressive behavior ( Jarrett et al 2014). It has been suggested that a combination of permissive and controlling/ hostile parenting styles may contribute to co-occurring anxiety and conduct problems (Granic 2014) and parent-focused treatments have been increasingly used for treatment of anxiety in children (Forehand et al 2013).…”
Section: Considerations For Future Researchmentioning
confidence: 99%
“…In each treatment, both children and parents participate to facilitate parents’ mastery of skills. In this randomized controlled trial, equivalence of outcomes between the two treatments was demonstrated (Ollendick et al, 2014). …”
Section: The Present Studymentioning
confidence: 97%
“…The present study enrolled families seeking treatment for their child's ODD symptoms (Ollendick et al, 2014). Families were randomly assigned to one of two treatment conditions: Parent Management Training (PMT: Barkley, 1997) or Collaborative and Proactive Solutions (CPS: Greene, 1998, 2010).…”
Section: The Present Studymentioning
confidence: 99%